2022
DOI: 10.1021/acs.chemmater.2c01105
|View full text |Cite
|
Sign up to set email alerts
|

Structural Influence on Exciton Migration and Singlet Oxygen Photosensitization in Porphyrinic Metal–Organic Coordination Networks

Abstract: A hexagonal three-dimensional (3D) metal−organic coordination network (MOCN) [(ZnTPyP)•0.75 DMSO] n (3D Helix) and a one-dimensional (1D) coordination polymer [(ZnTPyP)•DMF] n (1D Ladder) (ZnTPyP = 5,10,15,porphyrinatozinc(II)) are prepared and their photophysical properties are investigated to assess their ability to promote efficient exciton energy migration through singlet−singlet annihilation processes and to photosensitize singlet oxygen ( 1 O 2(g) ). The presence and absence of annihilation in 3D Helix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…As reported by Asselin et al, structurally enhanced energy migration can induce enhanced singlet oxygen photosensitization due to exciton migration from the mass toward the interface . Indeed, as reported in Figure , singlet oxygen generation is rendered obvious using TFT-MOF as a photosensitizer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by Asselin et al, structurally enhanced energy migration can induce enhanced singlet oxygen photosensitization due to exciton migration from the mass toward the interface . Indeed, as reported in Figure , singlet oxygen generation is rendered obvious using TFT-MOF as a photosensitizer.…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Asselin et al, structurally enhanced energy migration can induce enhanced singlet oxygen photosensitization due to exciton migration from the mass toward the interface. 58 Indeed, as reported in Figure 14, singlet oxygen generation is rendered obvious using TFT-MOF as a photosensitizer. Such solid−gas interface signals for O 59 So after collision with the surface of the photosensitizer, a maximum distance of 26.4 cm may be traveled by 1 O 2 (g) if in a straight line.…”
Section: Estimating the Rate Of Energymentioning
confidence: 99%
“…More recently, MOF glasses, a disordered form of MOFs, are finding niche applications. This virtual collection catalogues recent MOF advances featured in Chemistry of Materials from 2022 to 2023, with an accompanying editorial by Laura Gagliardi and Omar Yaghi that outlines three critical future directions for MOFs …”
Section: Opening Remarksmentioning
confidence: 99%
“…Harvey and co-workers assessed the ability of porphyrin-based MOFs to promote efficient exciton energy migration through singlet–singlet annihilation processes and to photosensitize singlet oxygen ( 1 O 2 ( g )). Interporphyrin couplings favor exciton migration determined by the Donor–Acceptor distance and orientation . In another insightful work on photoactive MOFs, D’Alessandro and co-workers quantified the temperature dependence of the kinetics of a double [2 + 2] photocyclization in photoactive [Cd 2 (stil) 2 (Py2TTF) 2 ] (stil 2– = 4,4′-stilbenedicarboxylic acid, Py2TTF = 2,6-bis­(4′-pyridyl)-tetrathiafulvalene) .…”
Section: Conductive and Photoactive Mofsmentioning
confidence: 99%
“…The efficiency of heterogeneous photocatalysis depends, among several parameters, on the efficiency (i.e., rate and distance) of exciton migration through the framework, which depends on the framework structure. , We now report the power dependence of the fluorescence intensity and lifetimes of 3D-[Zn 2 (BTTB)­(DMF) 2 •(H 2 O) 3 ] n hereafter designated MOF-D (for which no photophysical properties have been reported so far) and MOF-5 as a function of solvent molecules inside the pores (guests). It is found that in both cases, these parameters are strongly dependent on the nature of the guest molecule.…”
Section: Introductionmentioning
confidence: 99%